Miniature Biodevices with Mighty Impact: the Current Applications and Future Challenges of Organ-on-Chip Technology - Kumar, Santosh; Dagli, Namrata; Haque, Mainul (Bangladesh Journal of Medical Science, 2023)
Abstract not available Bangladesh Journal of Medical Science Vol. 22 No. 04 October’23 Page :725-728